Engineering optimization problems - Ramakrishnan Sivasankar (Nanyang Technological University, 2020)
This project aims to solve engineering optimization problems using the differential evolution method. In this report, overview, and general procedures on the Differential Evolution is discussed and various constraint handling methods were discussed. The optimization codes were written in python.